La Hora de Comer = Mealtime - Quinlivan, Ada; Vega, Eida de la; Aguilera, Aurora (Aurora Angelica) (New York : PowerKids Press, 2017)
Simple bilingual text and illustrations follow a fun and relatable character from meal to meal throughout their day.
Keywords: Food -- Juvenile literature; Dinners and dining -- Juvenile literature